2000
DOI: 10.1001/archotol.126.5.665
|View full text |Cite
|
Sign up to set email alerts
|

Intraosseous Ganglion of the Temporomandibular Joint Presenting With Otorrhea

Abstract: A ganglion cyst of the temporomandibular joint is a rare entity that commonly presents as a minimally tender, preauricular mass. This benign cystic lesion, which is lined by synovium and can be found in association with other joints, occasionally erodes adjacent bone to form an intraosseous ganglion. We discuss an unusual case of an intraosseous temporomandibular ganglion cyst that presented with bloody otorrhea. Examination revealed an external auditory canal mass with radiographic evidence of temporal bone e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 9 publications
0
27
0
Order By: Relevance
“…Ali et al 2 reported the case of a patient with a TMJ ganglion cyst who presented with auricle paresthesia that was thought to have arisen from compression of the auriculotemporal nerve. Albright et al 1 previously described a patient with a synovial cyst arising from the TMJ who had erosion of the temporal bone into the external auditory canal. Otherwise, symptoms from cysts arising from the TMJ have been relatively confined to the location of origin, with local symptoms such as pain, clicking with jaw opening, or limited range of jaw motion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ali et al 2 reported the case of a patient with a TMJ ganglion cyst who presented with auricle paresthesia that was thought to have arisen from compression of the auriculotemporal nerve. Albright et al 1 previously described a patient with a synovial cyst arising from the TMJ who had erosion of the temporal bone into the external auditory canal. Otherwise, symptoms from cysts arising from the TMJ have been relatively confined to the location of origin, with local symptoms such as pain, clicking with jaw opening, or limited range of jaw motion.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Ganglion cysts arising from the TMJ are more common in middle-aged women than in men or women of other ages, and patients with these lesions usually present with swelling and minimal to no pain in the preauricular area. 1,4,6,8 We report the case of a patient with a large ganglion cyst of the TMJ with unilateral intracranial extension in whom facial nerve palsy was the initial presenting symptom. We believe this is the first such case reported in the literature.…”
mentioning
confidence: 99%
“…The TMJ is a synovial joint with more than 50 cases of (extraneural) cysts reported in the literature. Extraneural cysts in this location can be asymptomatic or symptomatic (causing neural symptoms due to extrinsic nerve compression 3,4,8,23,33 or mastication difficulties because of the mass 2,7,20,32 ). They are derived from the TMJ via non-neural pedicles and can extend in different directions, even intraosseously 2,8,16,26 or intracranially 18,23,33 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…If symptoms clearly attributable to the ganglion cyst are present, complete resection of the TMJ ganglion cysts, along with any component in the EAC, can provide relief in cases with severe associated symptoms. 1, 5 …”
Section: Discussionmentioning
confidence: 99%